Green Economy: Connecting the dots - Susanne Dröge; Nils Simon (Stiftung Wissenschaft und Politik (SWP), 2011)
In June 2012 the international community will meet in Rio de Janeiro for the United Nations Conference on Sustainable Development (UNCSD, or Rio+20). One of the two main themes will be the »green economy in the context of sustainable development and poverty eradication«. To date, however, there is no consensus on what a »green economy« actually means or how it can be achieved. The European Union has proposed adopting a Green Economy Roadmap in Rio to help drive the global economy's transformation towards sustainability. Industrialised nations have already devised complementary approaches, including the OECD's Green Growth Strategy, which focuses on the compatibility of environmental protection and economic growth. In emerging economies and developing countries, concepts dominating the debate are »green development« schemes that place more weight on social issues. However, and notwithstanding these commitments, sustainability considerations play at best a subordinate role in the Europe 2020 strategy or G20 declarations. Yet it is imperative that the green economy is also discussed in committees and departments that significantly influence the real economy and capital markets. Otherwise a transformation towards a socially just and environmentally friendly global economy cannot succeed
Keywords: 320